Do Theory of Mind and Mental Time Travel abilities build on joint cognitive foundations? - Lydia Paulin Schidelko; Leonie Baumann; Marina Proft; Hannes Rakoczy (Royal Society Open Science)
Higher cognition is special in that it goes beyond representing the here and now. Two relevant forms of such thinking are Theory of Mind (ToM) that enables us to represent others’ perspectives, and Mental Time Travel (MTT) that enables us to represent other points in time. The present studies investigate how these capacities are related in development. Do they build on the same cognitive foundations and thus emerge together? Do higher-order forms of the two abilities rely on analogous recursive embedding and thus progress in parallel and coordinated ways? We addressed these questions in four studies with 3- to 9-year-old children (N = 395). ToM was operationalized as first-, second- and third-order false belief understanding. MTT was operationalized as reasoning about future possibilities (first-order), counterfactual reasoning (second-order) and anticipating counterfactual emotions (third-order). Study 1 shows a stepwise development of both ToM and MTT and a moderate consistency of performance patterns. However, across all four studies, we did not find robust correlations between first-, second- and third-order tasks of ToM and MTT, respectively. Overall, these results show stepwise and parallel trajectories in ToM and MTT, but do not provide stringent evidence for a joint cognitive foundation of the two capacities.